2011
DOI: 10.1080/01924788.2011.625213
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Mobility and Occupational Participation Outside the Home in Old Age Is an Act of Negotiation

Abstract: Facilitated by mobility, occupational participation outside the home is vital in old age. However, the relative importance of factors influencing mobility and occupational participation remains unclear. The present study describes older peoples' motives for, and experiences of, mobility and occupational participation outside the home. Nine focus-group interviews were conducted and analyzed using content analysis. Occupational participation and mobility was individually experienced, although some subjective per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…People with chronic pain 252 Hitch et al engage in both meaningful and mundane occupations, to maintain connectedness with the social world (van Huet, 2011). Similarly, elderly people reported virtual and media related mobility (via television, radio, and computers) contributed to their belonging by enabling connection with their community (Fristedt et al, 2011). While these findings suggest the nature of the relationship, both focus on populations who are socially isolated.…”
Section: Doing ↔ Belongingmentioning
confidence: 81%
“…People with chronic pain 252 Hitch et al engage in both meaningful and mundane occupations, to maintain connectedness with the social world (van Huet, 2011). Similarly, elderly people reported virtual and media related mobility (via television, radio, and computers) contributed to their belonging by enabling connection with their community (Fristedt et al, 2011). While these findings suggest the nature of the relationship, both focus on populations who are socially isolated.…”
Section: Doing ↔ Belongingmentioning
confidence: 81%
“… [ 111 ] Brazil Not reported Cross-sectional 1652; 60+ To evaluate the association between safety from crime and physical activity among older adults [ 112 ] Europe Urban Longitudinal 261; 75–81 To identify the effect of environmental facilitators for outdoor walking on development of walking difficulty in community-dwelling older people. [ 113 ] Europe Not reported Qualitative 957; 81.7 To describe older people’s motive for and experiences of mobility and occupational participation outside the home. [ 114 ] USA Urban Qualitative 21; 60+ To identify the salient factors of the neighborhood environment that encourage or discourage walking in older, urban African Americans.…”
Section: Resultsmentioning
confidence: 99%
“…The mediums through which people belong to groups (professional or otherwise) are currently undergoing changes. The role of technology was captured in a study of elderly people (Fristedt, Björklund, Wretstrand, & Falkmer, 2011), who found it to be a potential barrier to belonging, negating the need to make direct contact. However, younger generations often prefer to connect and belong through online mediums.…”
Section: Belongingmentioning
confidence: 99%